Persepsi Masyarakat terhadap Pendidikan Tinggi Keagamaan Islam Swasta di Dusun Ngagrong Kelurahan Wonolelo Kecamatan Sawangan Kabupaten Magelang - Tursila Tursila; Mukhlis Fathurrohman; Mu’in, Abdullah Abdullah (Departement of Mathematics Education, 2023)
Education is a very important factor for society in ensuring its survival. Education cannot be separated from its relationship with society. The problem is that there is a perception that education does not necessarily guarantee a bright future. This is evidenced by a large number of unemployed college graduates, which causes a wrong perception of education. From this background, the researcher wanted to discuss it in a thesis and took the Public Perception of Private Islamic Higher Education in Ngagrong Hamlet, Wonolelo Village, Sawangan District, Magelang Regency. This research uses a descriptive qualitative approach. The data collection techniques used are observation, interview and documentation methods, sorting them out to answer the problem formulation and then looking for and finding the meaning related to the problem formulation. The results of this study show that the perception of the people of Ngagrong Hamlet towards private Islamic religious higher education is quite good, that education can make their lives prosperous in the future. Therefore, this should be supported by quality abilities in the form of knowledge from higher education and the ability to practice in the community. Most public perceptions support their sons and daughters to pursue private Islamic religious higher education. The level of education of the people of Dusun Ngagrong is relatively high, although. However universities are still very minority, but the majority of the younger generation is now continuing their education from the junior high class, and upper middle class to college.